KEPEMILIKAN TERKONSENTRASI DAN CORPORATE GOVERNANCE PADA AGRESIVITAS PAJAK : BUKTI DARI PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI - Heni Yusnita; Warsih Ayu Wandira (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The main purpose of this study is to determine and analyze the effect of concentrated ownership, independent commissioners and partial audit quality on tax aggressiveness.This study uses secondary data originating from the BEI website using purposive sampling technique to select a research sample of 13 manufacturing sector companies in the Consumer Goods Industry Sector from 32 companies listed on the IDX in 2016-20120 The analytical method used is the multiple linear regression analysis method. Aggressiveness in this study was measured using ETR (Effective Tax Rate). The results of this study indicate that the variable ownership concentrated has no effect on tax aggressiveness. Independent Commissioner and audit quality have a significant positive effect on tax aggressiveness.